Studies in Nietzsche and the Classical Tradition - O'Flaherty, James C.; Sellner, Timothy F.; Helm, Robert M. (UNC Studies in the Germanic Languages and Literatures, 1976)
These fifteen essays deal with Nietzsche's view of various aspects of classical antiquity as compared to those of Augustine, Thomas Aquinas, Dante, Voltaire, Winkelmann, Hamann, Goethe, Schiller, Heine, Byron, the "fin de siècle" Decadents and others. An introductory essay by classical scholar H. Lloyd-Jones plus two essays on Nietzsche's aesthetics by W. Kaufmann and K. Weinberg round out the contributions by M. L. Baeumer, E. Biser, M. Boulby, S. L. Gilman, P. Heller, R. M. Helm, M. Hester, R. S. Fraser, J. C. O'Flaherty, H. Rehder, K. Schlechta, and H. Wingler.